The Driving Factors of Carbon Emissions in China’s Transportation Sector: A Spatial Analysis - Xu, Xingbo; Xu, Haicheng (Frontiers in Energy Research, 2021)
Relevant studies on the CO2 emissions from transportation sector in China are increasing, but the conclusions drawn from these studies are inconclusive. The main reason is that the spatial correlation of the CO2 emissions from the regional transportation sector is ignored when examining the driving factors of the CO2 emissions from the transportation sector. Therefore, this paper adopts new emissions factors to calculate the CO2 emissions levels from the transportation sector in Chinese provinces. By fully considering the spatial correlation of regional CO2 emissions and based on the two-way Durbin model with both spatial and temporal fixed effects, this paper studies the driving factors of the CO2 emissions from the transportation sector in China. Based on the CO2 calculation and spatial regression results for the transportation sector in China, (1) most of the regions with the highest CO2 emissions from the Chinese transportation sector are located on the east coast and gradually spread to the central and western regions. (2) The CO2 emissions from the transportation sector in South China are higher than those from the transportation sector in North China, and the regions with higher CO2 emissions gradually move from north to south. (3) Transportation activity intensity, urbanization level, technological level, industrial structure and per capita GDP greatly impact the CO2 emissions from the transportation sector in each province of China. Among these factors, transportation activity intensity, urbanization level, and per capita GDP exert not only direct but also indirect effects, while the technological level and industrial structure only exerts direct effects.